Association between serum albumin and 42-day postpartum mortality in women with acute fatty liver of pregnancy: a retrospective study - Fang, Yuxin; Liao, Guangyuan; Li, Xiangbin; Fang, Yi; Gao, Yuanmei (Frontiers in Medicine, 2025)
IntroductionAcute Fatty Liver of Pregnancy (AFLP) is a rare, life-threatening complication during pregnancy, characterized by acute liver failure, endangering both mother and fetus. Albumin (ALB), synthesized by the liver, is vital for maintaining plasma oncotic pressure and transporting substances, acting as a liver function indicator. Given the scarce research on the link between serum albumin levels and adverse outcomes in AFLP, our study aimed to explore the association between serum albumin levels and 42-day postpartum mortality in women with AFLP.MethodsThe study included 139 women with AFLP from the Third Affiliated Hospital of Guangzhou Medical University, from 2010 to 2022. Severe hypoalbuminemia is albumin <25 g/L; patients categorized as ≥25 or <25 g/L. Multivariable Cox proportional hazards regression analyses examined the relationship between serum albumin levels and 42-day postpartum mortality. The main outcome was mortality through 42 days postpartum, with secondary outcomes including maternal complications and fetal outcomes.ResultsOf the participants (average age 30.1 ± 5.4, 60.4% primiparous, the median gestational age was 36.1 ± 3.1 weeks), there were 15 deaths within 42 days postpartum, 10.8% mortality rate. After adjustment, multivariable Cox proportional hazards regression showed that patients with severe hypoalbuminemia faced a markedly higher risk of 42-day postpartum mortality (HR = 5.55, 95% CI 1.5 20.5). Multiple organ dysfunction and hepatic encephalopathy were more common in the ALB < 25 g/L group. Fetal death and low birth weight were associated with low serum albumin, though not significantly.ConclusionHypoalbuminemia serves as a critical and alterable risk factor for postpartum adverse complications related to AFLP.